Between Reductionism and Quest for Fullness. Integral Understanding of a Man as a Basis for an Ethical Discussion - Wadowski, Jan (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
A late modernity is an age of the extremes. They are marking: reductionism (1), technologizing (2) and massification (3). Consequences of reductionism in understanding the man are negative for him and for surroundings. On such an anthropological theory, assuming determined metaphysics, based a majority of researches in the problem of the good and evil. However in the humanistic sciences integral theories are more often popular, what is probably results from unconscious seeking the plenitude. In order to undertake versatile presentations of the good and evil, anthropological concepts diverse and using up, though not arbitrarily are necessar.